Effectiveness of Website-Based Counseling Application Using Forward Chaining to Improve Counselors’ Decision-Making Ability - Khairiyah Khadijah; Isnaria Rizki Hayati; Dian Oktary; Filma Alia Sari (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This research is motivated by the importance of the ability of Guidance and Counseling (BK) teachers to make appropriate, systematic, and data-based service decisions in schools. In practice, decision-making for BK services still often depends on subjective experience, so supporting media are needed that can help BK teachers in analyzing problems and determining alternative services. This study aims to determine the effectiveness of the use of website-based counseling applications with the forward chaining method in improving the decision-making ability of BK teachers in Dumai City schools. This study uses a quantitative approach with quasi-experimental methods and one-group pretest-posttest design. The research sample consisted of 50 BK teachers in Dumai City schools. The instrument used was a questionnaire on the decision-making ability of BK teachers given before and after the use of the application. Data were analyzed using descriptive statistics, paired sample t-test, and N-Gain. The results showed that the average pretest score of 43.84 increased to 83.26 in the posttest, with an average increase of 39.42. The results of the paired sample t-test showed a significant difference between the pretest and the posttest, which was obtained from the results using the SPSS Application, namely t calculation = 59.98 and p-value 0.001 < 0.05. The average N-Gain value of 0.704 or 70.39% is in the high category. Thus, a website-based counseling application with the forward chaining method is effectively used to improve the decision-making ability of BK teachers in schools